Implementation of a Sharia-Based Management System at the Muhammadiyah Zakat, Infaq, and Sadaqah Institution (LAZISMU) of Pamekasan Regency - Syukriatus Sholeha; Khairul Jannah (CV Edujavare Publishing, 2026)
This study examines the implementation of a Sharia-based management system at the Muhammadiyah Zakat, Infaq, and Sadaqah Institution (LAZISMU) of Pamekasan Regency. The research aims to analyze how Sharia principles are integrated into the institution's managerial practices and to assess their contribution to effective zakat governance. A qualitative case study approach was employed. Primary data were collected through semi-structured interviews with LAZISMU management, supported by observations and document analysis. Data were analyzed using the interactive model of data condensation, data display, and conclusion drawing, while source and method triangulation were applied to ensure the credibility of the findings. The results indicate that LAZISMU has implemented a Sharia-based management system by integrating the principles of amānah (trustworthiness), ṣidq (truthfulness), transparency, accountability, justice, and compliance with Islamic law into its organizational governance. The institution systematically classifies Zakat, Infaq, and Sadaqah (ZIS) funds according to their respective Sharia provisions, utilizes multiple collection channels—including digital payment platforms and QRIS—and applies transaction verification procedures to strengthen accountability. Financial administration is supported by the Fiscal Management Information System (SIM Fiskal), while periodic reconciliation and financial reporting are conducted in accordance with PSAK 109 on Accounting for Zakat, Infaq, and Sadaqah. These practices demonstrate the successful integration of Islamic ethical values with modern management and accounting standards, resulting in enhanced organizational transparency, operational efficiency, and public trust. This study concludes that the implementation of a Sharia-based management system has significantly contributed to strengthening institutional governance and improving the effectiveness of zakat management at LAZISMU Pamekasan Regency. The findings provide practical implications for zakat management institutions seeking to enhance accountability and public confidence while maintaining full compliance with Sharia principles.